1877 Terr. of Dakota Rev. Codes 794, Penal Code, ch. 38, § 455 - (:unkn) unknown (General Publisher, 1877)
Prohibited the manufacture, sale, giving, or disposing of any instrument or weapon usually known as a slungshot, or similar weapon.Violators guilty of a misdemeanor.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS